Development of a pulse solenoid of magnetic field amplitude up to 0.5 T and a pulse sinusoidal current generator for its power supply - Reshetnyak, N.G.; Romasko, V.P.; Chertishev, I.A. (Вопросы атомной науки и техники, 2020)
The magnetic system of the installation to control the transverse dimensions of an electron beam formed by a magnetron gun with a secondary emission cathode was updated. An additional solenoid with pulsed power supply located in a vacuum chamber at a distance of 0.05…0.1 m from the gun’s edge will be used in experiments. The solenoid design was selected and calculated. Possibility of a magnetic field generation of amplitude of up to 0.5 T at amplitude of the pulse current of ~ 1.5 kA, was demonstrated. The field has a uniform area at the level of ± 5% over the length of ~ 0.2 m. Проведено модернізацію магнітної системи установки для управління поперечними розмірами електронного пучка, формованого магнетронною гарматою з вторинно-емісійним катодом. У дослідженнях буде використано додатковий соленоїд з імпульсним живленням, що розташований у вакуумній камері на відстані 0,05…0,1 м від зрізу гармати. Проведено вибір і розрахунок конструкції соленоїда. Показана можливість отримання магнітного поля з амплітудою до 0,5 Тл, при амплітуді імпульсного струму ~ 1,5 кА. Поле має однорідну частину на рівні ± 5% на довжині ~ 0,2 м. Проведена модернизация магнитной системы установки для управления поперечными размерами электронного пучка, формируемого магнетронной пушкой с вторично-эмиссионным катодом. В экспериментах будет использован дополнительный соленоид с импульсным питанием, расположенный в вакуумной камере на расстоянии 0,05…0,1 м от среза пушки. Проведен выбор и расчет конструкции соленоида. Показана возможность получения магнитного поля с амплитудой до 0,5 Тл, при амплитуде импульсного тока ~ 1,5 кА. Поле имеет однородную часть на уровне ± 5% на длине ~ 0,2 м.